The Modern Health Dualism: The Path to Beatitude Between Angels & Machines - Trnavac, Vuk P. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
In this paper, the author, first of all, tries to examine how the modern concept of Health in the opinions of philosophers (rationalists – idealists) in focus, including their exchange of opinions with materialistically oriented philosophers, relates to Transcendence. On the other hand, in the context of these two key terms, it is also necessary to determine the attitude of these philosophers towards the mechanistic world view, which was then in full development. The author’s opinion is that the eudaimonistic position in the philosophy of health of this period is, actually, the central path that is established through a sharply set modern era’s Cartesian dualism, on the one hand, the Spirit which in self-relation, as a composite subject of two (finite) substances, and towards its own (human) Soul as a substantial form, and in the ultimate sense also towards God as a Transcendent (the one that transcends us) Being. The other side of this dualism belongs to the Basic, infinite substance of the Body, which somehow, but, regardless of the primacy of Spirit, must be able to follow and physically carry the Spirit.
Keywords: Health; Transcendence; modern philosophy; Rationalism; Spirit; Soul; Body